Diurnal nectar secretion dynamics in Roscoea cautleoides (Zingiberaceae) reveal the role of non-sugar chemicals in plant–pollinator interaction - Wen-Jing Wang; Ya-Ting Lin; Hong-Fan Chen; Mei-Yuan Huang; Zong-Xin Ren; Jian-Li Zhao (Current Plant Biology)
Floral nectar is essential for plant-pollinator interactions, directly influencing plant reproduction. Although the composition of nectar has been widely studied, the daily dynamics of non-sugar components in the nectar remain unknown. In this study, we investigated the diurnal dynamics of nectar volume, composition, and pollinator visitation in an alpine ginger (Roscoea cautleoides). By integrating metabolomics and transcriptomics, we explored the daily variations in nectar chemical composition and the gene expression in nectaries, with a specific focus on nectar metabolites from bagged flowers. We found that the nectar volume peaked at ∼2.5 μL per flower in the early afternoon, whereas the pollinator visitation attained its highest level in the late afternoon. Meanwhile, the nectar volume in bagged flowers increased by ∼40 % from morning to afternoon but consistently remained lower than that of flowers exposed to pollinator visitation. While sugar content remained stable throughout the day, non-sugar metabolites varied significantly. Notably, daily variations in arachidonic acid levels were positively correlated with the expression of the RcSUZ gene in nectaries, suggesting a molecular link between non-sugar metabolites and gene regulation. These findings indicate that non-sugar metabolites may serve as a rapid response mechanism to pollinator visitation, potentially modulated by gene expression. Moreover, the results further demonstrate that R. cautleoides flowers rapidly adjust their nectar chemistry in response to pollinator behaviour in a day, providing valuable insights into the molecular and ecological mechanisms underlying plant-pollinator interactions and reproductive adaptations.